Early lessons from COVID‐19 that may reduce future emergency department crowding. (16th September 2020) - Mazurik, Laurie; Javidan, Arshia P; Higginson, Ian; Judkins, Simon; Petrie, David; Graham, Colin A; Bonning, John; Hansen, Kim; Lang, Eddy
Abstract: The COVID‐19 pandemic has produced significant changes in emergency medicine patient volumes, clinical practice, and has accelerated a number of systems‐level developments. Many of these changes produced efficiencies in emergency care systems and contributed to a reduction in crowding and access block. In this paper, we explore these changes, analyse their risks and benefits and examine their sustainability for the future to the extent that they may combat crowding. We also examine the necessity of a system‐wide approach in addressing ED crowding and access block.